Realizing Sustainable Agriculture in Bali: How Land-Use Conversion Impacts The Future of Food Security and Local Culture in Tabanan - Yasmita, I Gusti Ayu Lia (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2025)
This study aims to highlight the challenges posed by this trend, propose strategies to mitigate its impact, and explore the potential of agritourism as a sustainable solution to preserve agricultural land while boosting the local economy. This study employs a descriptive qualitative method and focused on case study in Tabanan Regency. Interviews were conducted with 20 respondent. The findings reveal that land-use conversion is critical issue requiring firm action and strong collaboration among the government, private sector, and farmer as landowners. The study continues to utilize a descriptive qualitative approach, with its scope confined to the Tabanan Regency area. Various alternatives and solution have been developed to mitigate land-use conversion, one of which is agrotourism. This approach is anticipated to support the sustainability of agricultural land while strengthening the local economy. Its holistic approach integrates land conversion issues, farmer welfare, agritourism, and government policies to devise sustainable solutions for regions experiencing significant land-use changes, such as Tabanan Regency.